H i observations of IC 10 with the DRAO synthesis telescope. Issue 3 (26th October 2019) - Namumba, B; Carignan, C; Foster, T; Deg, N
ABSTRACT: H i observations of the nearby blue compact dwarf galaxy IC 10 obtained with the Dominion Radio Astrophysical Observatory synthesis telescope, for a total integration of ∼1000 h, are presented. We confirm the NW faint 21 cm H i emission feature discovered in Green Bank Telescope (GBT) observations. The H i feature has an H i mass of 4.7 × 10 5  M⊙, which is only ∼0.6 ${{\ \rm per\ cent}}$ of the total H i mass of the galaxy (7.8 × 10 7  M⊙ ). In the inner disc, the rotation curve of IC 10 rises steeply, then flattens until the last point where it rises again, with a maximum velocity of 30 km s −1 . Based on our mass models, the kinematics of the inner disc of IC 10 can be described without the need of a dark matter halo. However, this does not exclude the possible presence of dark matter on a larger scale. It is unlikely that the disturbed features seen in the outer H i disc of IC 10 are caused by an interaction with M 31. Features seen from our simulations are larger and at lower surface density than can be reached by current observations. The higher velocity dispersions seen in regions where several distinct H i features meet with the main core of IC 10 suggest that there is ongoing accretion.